2008
DOI: 10.1300/j514v19n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior, Mental Health, Substance Use, and HIV Risk Among Agency-Based Male Escorts in a Small U.S. City

Abstract: Relatively little research has examined the personal sex lives of indoor male sex workers (MSWs) or possible connections in this group between sexual behavior and factors related to HIV risk. As part of a larger project, this study collected data from 30 agency-based indoor MSWs (mean = 22.4 years) about their sexual behavior, mental health, and substance use. Few HIV risk behaviors with clients occurred. Drug use and mental health problems were relatively frequent, but not related to increased risk behavior. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
4
23
1
Order By: Relevance
“…Perhaps this situation is related to the high level of illegal immigration associated with the sex trade. On the other hand, economic factors play an important role in determining sexual behaviors with clients (Smith & Seal, 2007), so illegal immigration and economical difficulties among MSWs could facilitate more sexual risk behaviors when clients offer more money if they perform unsafe sex acts. In our study, MSWs told the authors that this amount of money is independent from the amount negotiated by the manager and the client previously and the MSW never talks about this amount of money received.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this situation is related to the high level of illegal immigration associated with the sex trade. On the other hand, economic factors play an important role in determining sexual behaviors with clients (Smith & Seal, 2007), so illegal immigration and economical difficulties among MSWs could facilitate more sexual risk behaviors when clients offer more money if they perform unsafe sex acts. In our study, MSWs told the authors that this amount of money is independent from the amount negotiated by the manager and the client previously and the MSW never talks about this amount of money received.…”
Section: Discussionmentioning
confidence: 99%
“…However, allowances were made for the MSWs to flexibly present their stories without interruption, as long as coverage of all required topics was accomplished (Hutchinson & Wilson, 1994). Data on sexual behavior with both clients and non-paying partners also was collected via a structured questionnaire, results which has been published elsewhere (Smith & Seal, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…As noted, data on the sexual behavior of study participants has been reported elsewhere (Smith & Seal, 2007). However, to summarize as a way of providing context for the current data regarding safer sex behavior with clients, 90% (n = 27) of MSWs reported that they engaged in oral or anal sex with a paying sexual partner in the prior 30 days (median = 3.0 partners).…”
Section: Hiv Sexual Risk Behaviorsmentioning
confidence: 96%
“…Client characteristics (e.g., familiarity with clients) affect condom use among FSW (Choi & Holroyd, 2007) but it is less certain whether such associations are significant among MSW (Mimiaga, Reisner, Tinsley, Mayer, & Safren, 2009). A study showed that substance use was associated with UAI during commercial sex among MSW, but the timing of substance use was not aligned with that of commercial sex (Smith & Seal, 2008b). Other contextual factors associated with UAI among MSW include availability of condoms, keepers', and peers' influences (Smith & Seal, 2008a, 2008b.…”
Section: Introductionmentioning
confidence: 99%